To the public : As the merchants of this city have nobly refused letting their vessels to the tools of government, for the base purpose of transporting troops and military stores to Boston ... it is therefore hoped that no pilot will be found so lost to all sense of duty to his country, as to assist in that detestable work . (LLMC-digital (Series), 1774)
Exhortation and warning not to provide goods or services to the British troops at Boston.